APPLICATION OF GUIDED INQUIRY LEARNING MODELS TO IMPROVE STUDENTS 'SOCIAL STUDIES LEARNING OUTCOMES CLASS IVA SDN 07 JATI MULYA - Tukiman (JURNAL RANDAI, 2021)
Based on the description of the table above, of the 28 grade IVA students of SDN 07 Jati Mulya (18 male students and 8 female students) who did not reach the minimum completeness criteria were 21 people, namely around 45% where classically they did not meet the completeness criteria set by the school 75%. Thus there are still many students who have not reached the minimum completeness criteria. So that the teacher has to repeat the same material over and over again for several meetings in an effort to improve student learning outcomes. This makes the demands of the curriculum not achieved because the time allocation that should be used for the next material is used to discuss the same material. Seeing this condition, the researcher considers it necessary to provide a learning model that can arouse students in learning. One learning model that leads to student curiosity and improves student learning outcomes is the guided inkuri learning model. Guided inkuri learning model is a learning activity that emphasizes the process of thinking critically and analytically to find and discover for themselves the problem that is being questioned to students. Social studies learning with inquiry is able to lead students to realize what they have obtained after learning. As for the formulation of the problem in this study is "Can the application of guided inquiry learning models improve social studies learning outcomes of class IVA SDN 07 Jati Mulya students?" This study aims to improve the social studies learning outcomes of grade IVA students of SDN 07 Jati Mulya by applying the Guided Inquiry learning model. Based on the results of the research and discussion carried out, it can be concluded that the application of the guided inquiry learning model can improve the learning outcomes of grade IVA students at SD Negeri 07 Jati Mulia, Kerinci Kanan District, Siak Regency, which is proven that student learning outcomes increase from the basic score, cycle I and cycle II. In the basic score, the class average was 63.75, increasing in the first cycle with an increase of 2.35% to 65.25. In the second cycle, the class average increased again with an increase of 8.00% to 74.25